Penggunaan Hadis Dalam Fatwa MUI Tentang Pluralisme: Telaah Kritis - Garwan, Muhammad Sakti (Living Islam: Journal of Islamic Discourses, 2019)
This article explores the meaning and existence of Hadith in the fatwa of the Indonesian Ulama Council (MUI). In this case the Hadith is not merely as a source of law in deciding a fatwa, but also reflects the basis of an argument about religion. As an influential religious institution, MUI determines a perception of the truth of religion offered to the community. At the same time, the paradigm of religio-centrism seems to prevent the institution from deciding on more inclusive fatwas. Therefore, the criteria of the hadith in the fatwas are based on the Ahlu Sunnah Wal Jama'ah. In other words, the fatwa tends to be oriented towards the Shafi'i which is approved by the majority of Muslims in Indonesia.